Textbook of toxicology - Pani, Balram (I K International Publishing, 2010)
Toxicology is a discipline that requires knowledge in many areas, such as analytical chemistry (organic and inorganic), biochemistry, pathology and physiology. This book is designed to provide a wide ranging, overview of the various toxicants and their effects on living organisms, particularly human begins. The book also examines the principles related to toxicology, chemical toxicology, environmental toxicology and related sciences.The book provides an up-to-date insight into the harmful interactions between chemicals (xenobiotics) and biological synthesis. It examines acute toxicology risk assessment, toxicity testing and many other areas directly or indirectly related to toxicology.